Calibration of Thermal Comfort Classes for Open Spaces in Subtropical Climate - Gobo, João Paulo Assis; Galvani, Emerson; Wollmann, Cássio Arthur; Gonçalves, Fabio Luiz Teixeira (Revista do Departamento de Geografia, 2018)
Thermal comfort index has been used to evaluate the average perception of people regarding weather conditions in several regions of the globe, although very little with respect to the subtropical region of Brazil, particularly in southern Brazil. Therefore, this study aimed to define a range of thermal comfort suitable for residents of the Santa Maria city, Rio Grande do Sul, based on perception / feeling questionnaires to the inhabitants, simultaneously to the meteorological data records between days 05 From August to August 7, 2015, from January 17 to January 19, 2016 and from July 6 to July 8, 2016. Primary data were collected on air temperature, gray globe temperature, relative humidity, wind speed, wind gust, global solar radiation and rainfall. Interviews were conducted on people aged between 18 and 60 years, with body coverage between 0.5 and 1.0 clo. In this study, it was concluded that the statistical modeling was effective in determining the thermal comfort ranges adequate to the climatic patterns and the thermal preference of the population of Santa Maria, Rio Grande do Sul. However, based on the statistical analysis applied, the conclusion is that none of these indexes, as originally constructed, in fact ideal for explaining the thermal comfort in Santa Maria, being necessary the adaptation of these, or a new index construction.